BIOETIKOS METODOLOGINIO PAGRINDO PAIEŠKA (I): DAUGIAPRINCIPINĖ PRIEIGA. - Bartkienė, Aistė (Problems / Problemos, 2011)
This is the first article out of two. In the first article poliprincipal approach to fundamental controversies in bioethics is represented. Even though it was started to deal with bioethical problems in the middle of XX century but the interest in methodological basis was clearly emphasized only in the end of it. In the field of bioethics a lot of new questions emerged and traditional theories of ethics appeared insufficient in order to answer those questions. This is one of the reasons why the quest for suitable principles employed in solving concrete bioethical problems started. On the other hand application of bioethical theories in practice exposed the need to find such an approach which could help to solve bioethical questions considering variety of moral convictions and reversed relationship between doctor and patient. New ways to solve these problems where looked for and in some instances thinkers even combined utilitarianism and deontology in one theory. While representing poliprincipal approach to bioethics it is claimed that these theories deducing bioethical principals out of everyday morality can not avoid inconsistency which is characteristic to everyday moral convictions and for that reason can not offer any fundamentally new and uncontroversial ways to solve bioethical controversies.